Intestinal microbiota-mediated dietary fiber bioavailability - Guo, Kangxiao; Yao, Zihan; Yang, Tao (Frontiers in Nutrition, 2022)
Dietary fiber refers to a kind of carbohydrates that can not be digested and absorbed by the human small intestine, and can be fermented in all or part of the large intestine and have a kind of healthy significance to the human body. With the improvement of living standards, people pay more and more attention to intestinal health, and the relationship between dietary fiber balance, intestinal microecological balance and body physiological balance and their molecular connection mechanism have become a research hotspot. This paper reviewed its mediated bioavailability in order to provide a basis for the rational classification of dietary fiber and provide guidance for the development of new healthy foods, the deep processing of food and its application.